Unexplained multi-sensory neuropathy syndrome in young Tanzanian adults - Enica R. Massawe; Ndeserua Moshi; Junkun Ren; Catherine C. Rieke; Albert K. Magohe; Abigail M. Fellows; Enat A. Arega; Christopher E. Niemczak; Brian P. Jackson; Margaret R. Karagas; Jay C. Buckey (Journal of Global Health Reports)
# Background A unique syndrome affecting young adults of unexplained hearing loss often associated with uncorrectable poor visual acuity and lower extremity numbness is endemic in Dar es Salaam. This study characterised the hearing loss, associated it with other symptoms, and gathered information on potential causes.